Study of Fuzzy Closure and Fuzzy Point - Abhishek Kumar Yadav,; Dr. R. N. Singh, (International Journal of Scientific Research in Science and Technology, 2024)
Three years after Zadeh introduced the notion of a fuzzy set in his seminal paper in 1965, the first paper of fuzzy topology, introduced by Chang, appeared in 1968. Atanassov introduced and studied the concept of intuitionistic fuzzy sets as a generalization of fuzzy sets. Coker came out with the concept called “intuitionistic fuzzy topological spaces”. Tong introduced and investigated strong forms of open sets called strong regular open, θ-open, and δ-open sets, respectively. In this present paper, we studied fuzzy closure and fuzzy point [1-5].
Keywords: Fuzzy Boundary; Reference Function; Topology